ALS deficiency caused by an exon 2 deletion and a novel missense variant in the gene encoding ALS. (October 2019) - Dominguez-Menéndez, Gonzalo; Poggi Mayorga, Helena; Arancibia, Mónica; Benavides, Felipe; Martinez-Aguayo, Alejandro
Abstract: Context: ALS deficiency (ACLSD), caused by mutations in IGFALS, is characterized by a mild short stature, low concentrations of IGF-I and IGFBP-3, and a normal growth hormone (GH) stimulation test response . To our knowledge, no larger deletions have been reported. Case description: A 17-year-old adolescent male was evaluated due to delayed puberty and short stature. He had a height of 154.4 cm (SDS -2.84), a weight of 53.3 kg (SDS -1.41), a BMI of 22.4 kg/m2 (SDS +0.31), a Tanner 2 pubertal stage with a testicular volume of 10 mL, and a bone age of 16 years (SDS -1.33). After biochemical evaluation, low IGF-I levels, undetectable IGFBP-3 levels, and a normal response to the GH stimulation test were observed, suggesting GH insensitivity. ACLSD was confirmed by ALS measurement (116 ng/mL, SDS -3.19) and genetic analysis of IGFALS . An apparently homozygous missense variant, p. Pro624Leu, was found in exon 2 of the proband; this mutation was observed on one allele of the proband's father but was absent in the mother and siblings. Deletion/duplication analysis by multiplex ligation-dependent probe amplification (MLPA) was consistent with a deletion encompassing a significant part of exon 2 on one allele in the proband and in his mother and siblings. Conclusion: This is the first report of a large deletion in a patient with ACLSD. Deletion/duplication analysis should be considered in the genetic study of ACLSD, especially when homozygosity for a pathogenic variant cannot be confirmed by the study of the parents or when no variants are found but ALS concentrations are very low. Highlights: Description of ACLSD novel genetic cause in the first reported Chilean patient. The first larger deletion involving exon 2 of IGFALS, demonstrated by MLPA. On the other allele we find a missense variant not described in a clinical context. In available relatives, some had one of the variants and reduced ALS concentration.